Reproductive function in premenopausal African blacks with metabolic syndrome: associations among Inhibin B, adipokines, pituitary and sex hormones and sex hormone binding globulin (2016)
Reproductive dysfunction is associated with metabolic syndrome. Since fertility is highly valued in Africa, preliminary data on the association of metabolic syndrome with indices of reproductive function in premenopausal Nigerian women was provided. Sixty six premenopausal participants (44 with metabolic syndrome and 22 controls) aged 18-45 years were purposely selected for this study. Reproductive history, blood pressure and waist circumference were obtained by standard methods. Fasting blood was obtained for pituitary hormones, adipokines, sex hormone and sex hormone binding globulin, and inhibin B assays by EIA, ELISA and electro-chemiluminiscence. Plasma glucose, triglycerides and high density lipoprotein cholesterol were estimated by enzymatic methods. Free androgen index and oestrogen-testosterone ratio were calculated. Data obtained were statistically significant at P<0.05. All reproductive factors except follicle stimulating hormone and free androgen index levels were similar in both groups (P>0.05). Leptin levels were higher while adiponectin levels were lower in MS group than controls (P<0.05). Reproductive function appears sustained in MS. However, altered adipokines may relate to MS.